Device for individual hand finger rehabilitation - Oliveira, Bruno Rodrigues de; Stoppa, Gabriel Percival; Stoppa, Marcelo Henrique (Brazilian Journal of Production Engineering, 2024)
Hands are indispensable when carrying out various everyday tasks. Situations such as car, work or vascular accidents impair mobility and hand maneuverability, forcing individuals to seek rehabilitation methods. This study proposes a low-cost device for finger rehabilitation that facilitates flexion/extension movements while respecting the physiological limits of each joint. The model utilizes a system of linear actuators to move the phalanges of the index finger, mimicking natural flexion. The study leverages mathematical modeling to determine the index finger’s trajectory during flexion, considering joint angles and phalanx dimensions. This modeling led to the development of a 3D prototype using free software, ensuring that the dimensions and movement of the mechanism respect the anatomical characteristics of the finger. The results demonstrate that the prototype achieves the working space limits of the index finger, performing controlled and precise flexion movements. The study also proves the feasibility of the device construction through 3D printing of parts and preliminary testing. Future steps include developing a mechanism control system, a patient safety system with an interface for programming movement repetitions and applied force, and expanding functionality to include other hand movements. This model shows promise as a finger rehabilitation tool, offering controlled and safe flexion movements.